Tissue-specific enhancement of OsRNS1 with root-preferred expression is required for the increase of crop yield - Gho, Yun-Shil; Choi, Heebak; Moon, Sunok; Kim, Sung-Ryul; Ha, Sun-Hwa; Jung, Ki-Hong (Elsevier, 2022)
Root development is a fundamental process that supports plant survival and crop productivity. One of the essential factors to consider when developing biotechnology crops is the selection of a promoter that can optimize the spatial–temporal expression of introduced genes. However, there are insufficient cases of suitable promoters in crop plants, including rice. This study aimed to verify the usefulness of a new rice root-preferred promoter to optimize the function of a target gene with root-preferred expression in rice. osrns1 mutant had defects in root development based on T-DNA insertional mutant screening and CRISPR technology. To optimize the function of OsRNS1, we generated OsRNS1-overexpression plants under two different promoters: a whole-plant expression promoter and a novel root-preferred expression promoter. Root growth, yield-related agronomic traits, RNA-seq, and reactive oxygen species (ROS) accumulation were analyzed for comparison. OsRNS1 was found to be involved in root development through T-DNA insertional mutant analysis and gene editing mutant analysis. To understand the gain of function of OsRNS1, pUbi1